Case Report: Application of Hypnopressure on the Smoothness of Breastfeeding and Breastfeeding Self-Efficacy in Teenage Mothers - Risti Linta Chumaira; Nina Setiawati (UIMA Press, 2024)
Background: Mother's milk is the best natural food a mother can give to her baby. Breastfeeding is influenced by age; the younger the mother's age, the more breastfeeding tends to become smaller. Consistent milk production and a sense of confidence in breastfeeding are essential to the success of exclusive milk delivery. Hypnopressure is one of the methods that can enhance and maintain milk production and breastfeeding confidence. Objectives: The purpose is to report the provision of nursing care based on evidence-based on the problem of smooth breastfeeding and breastfeeding self-efficacy in teenage mothers. Methods: Case studies by implementing evidence-based practice in nursing care. The study was conducted on two teenage breastfeeding mothers who had problems with breastfeeding fluency and breastfeeding self-efficacy. Results: The primary outcome of this study will be the effect of the intervention on breastmilk production and breastfeeding confidence in teenage mothers. We conclude that hypnopressure could improve breastmilk production (92,8% and 85,7%) and breastfeeding confidence (55 and 57) Conclusion: Implementing evidence-based practice related to hypnopressure can smooth breastfeeding and improve its effectiveness in adolescent mothers.